2020
DOI: 10.1002/pc.25865
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of cellulosic‐based Polyalthia longigolia seed filler reinforced vinyl ester biocomposites on tribological performance

Abstract: The focus of this work was to analyze the effect of weight percentage (wt%) of Polyalthia longigolia seed filler (PLSF) on the wear responses (wear loss and coefficient of friction) of the vinyl ester (VE) matrix composites, using signal‐to‐noise (SN) ratio and analysis of variance (ANOVA) methods. The Polyalthia longigolia seed filler/vinyl ester (PLSF‐VE) composites were produced by compression molding (CM) technique. Scanning electron microscopy (SEM) analysis showed that the PLSF content was homogeneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The immersion duration of ZnO NPs together into sensitizing dye had been demonstrated to be an important factor in the solar cell properties of the ZnO-based DSSC [34]. When compared to similar research [12][13][14][15], the manufactured ZnO-based DSSC showed better performance in a lesser period of sinking time [35][36][37][38][39][40][41][42][43][44]. The enhanced absorption due to the larger amount and the better performance can also be expressed by the dye molecules that have been adsorbed onto the ZnO surface which can also expressed the better performance.…”
Section: X-ray Diffraction Analysis the Xrd Pattern Of Znomentioning
confidence: 99%
“…The immersion duration of ZnO NPs together into sensitizing dye had been demonstrated to be an important factor in the solar cell properties of the ZnO-based DSSC [34]. When compared to similar research [12][13][14][15], the manufactured ZnO-based DSSC showed better performance in a lesser period of sinking time [35][36][37][38][39][40][41][42][43][44]. The enhanced absorption due to the larger amount and the better performance can also be expressed by the dye molecules that have been adsorbed onto the ZnO surface which can also expressed the better performance.…”
Section: X-ray Diffraction Analysis the Xrd Pattern Of Znomentioning
confidence: 99%
“…This could be predictable to number of ions in the nanoparticles superficial fustily increases as crystal size declines. Moreover, as shown in Figure 5, the trailer recombination rate rises as the size declines due to the increase in intersection between the electron (e-) and hole (P+) with increasing volume of ZnO NPs of 10 g, 15 g, 20 g, and 25 g [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Photoluminescence (Pl) Spectral Analysismentioning
confidence: 99%
“…After that, the inhibition zone around the well was calculated and recorded. The tests were done in triplicates [ 31 34 ].…”
Section: Methodsmentioning
confidence: 99%